Understanding the importance of biodiversity and conservation and its symbiotic relation with mankind based on international and national legal setting / Mohamad Sabri Yusof - Yusof, Mohamad Sabri (Universiti Teknologi MARA Cawangan Pahang, 2019)
The livelihood of mankind, this generation and the other generation to come is interdependent on how we appreciate and approach the environment and the many abundance pool of biodiversity around the globe. Mankind must acknowledge the problem that was created due to the over exploitation of the earth biodiversity for commercial short term benefit; and try our very best to ratify our mistake through a regime of positive action that are more sustainable in nature. Concerted measures must be taken by all state actors to implement agreed international environmental law and policy at both global and national level.